The Role Evaluative Vocabulary in Media Texts Devoted to Economy of the Danube Region: Array - Chetverikova, Olena (Journal of Danubian Studies and Research, 2020)
Modern media resources occupy a prominent place in the professional activities and everyday life of man. Mass communication, along with the development of high-tech production, has become widespread. Therefore, the linguistic study of the on-line media, embracing all the spheres of life of the world community, including its economic development, is becoming one of the most promising areas of humanitarian knowledge. Any product involves assessing its quality through specific vocabulary. Evaluative phenomena play an important role in the communicative process. The linguistic implementation of evaluation presupposes the use of various lexical units with evaluative meaning in the semantic word structure. We also pay attention to the use of elements that enhance the influence of evaluative words.